Openness to experiences/ Curiosity helps people handle stress better? An empirical study among emergency services workers in Gujarat - Sinha, Neeta; Pal, Supriya (International Journal of Psychosocial Rehabilitation, 2020)
Emergency workers have to be available 24 x 7 to provide help to victims in crisis. They work round the clock in order to provide the best possible help to victims in all possible and traumatic situations. Being on call 24x7 these workers hardly have any ‘me’ time let alone any social or family time. This paper aims to explore the relationship between ‘Openness to experience’ factor of the ‘Big Five’ personality model and stress that the women at emergency services undergo at Women Helpline (WHL) across Gujarat. Data was collected using the Organizational Role Stress (ORS) Scale by Pareek (1983) and Big Five Questionnaire was administered to check the personality type of the employees. Big five comprises of five factors but for the purpose of this study only ‘Sociability’ (Extraversion) and its effect on stress levels was used. To analyze the results Chi-Square was run. Results revealed that openness to experience is associated with four out of ten role stress factors.